Pelestarian Tradisi Pembuatan Sesajen sebagai Media Pendidikan Karakter di Desa Sempu Ngebel Kabupaten Ponorogo - Muhammad Yusuf Nadhifa; Muhammad Misbahuddin (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study was conducted to explain how Islam and local Islamic education influence the success of Islamic preaching in Sempu Village. The Sempu Village community is known to uphold local customs and cultural values, which then become strategic tools in conveying Islamic teachings. Through cultural approaches such as sedekah bumi (earth alms), selametan (celebration), regular Yasinan (recitation of the Yasin), and reog (reog) performances, local preachers and religious leaders can convey Islamic messages more effectively and be accepted by the community. The research method used is the ABCD Method. This method focuses more on an in-depth understanding of phenomena, opinions, and perceptions. Qualitative methods involve techniques such as interviews, participant observation, text analysis, and case studies. The goal is to understand the social, cultural, and psychological context surrounding the subjects studied in the Sempu Village community. And through the community service that has been implemented, students have a better understanding of the cultural diversity of each village.